Impact of lateral boundary conditions on precipitation and temperature extremes over South Korea in the CORDEX regional climate simulation using RegCM4 - Oh, Seok-Geun; Suh, Myoung-Seok; Cha, Dong-Hyun (Asia-Pacific journal of atmospheric sciences, 2013)
In this study, the impact of lateral boundary conditions (LBCs) on the simulation skills of the climate model RegCM4 for extreme climate events (ECEs) over South Korea are investigated using two sets of 20-yr (1989–2008) integration with two LBCs (ERA and R-2). The ECEs were defined by a percentile method and an absolute threshold method. In general, RegCM4 successfully reproduces the spatial distribution and the inter-annual variability (R > 0.76) of ECEs indices (precipitation and temperature extreme 5%) irrespective of LBCs. When driven by ERA, RegCM4 shows better simulation skill for ECEs (PR5%, TX5%, hot days, tropical nights, and wet days) than when driven by R-2. The ERA run simulates more than +7 mm day −1 and +1.1°C for PR5% and TX5% than those by the R-2 run, respectively. Although RegCM4’s simulation skills for the ECEs defined by absolute thresholds are significantly different according to LBCs, RegCM4 captured the interannual variability of frost days, hot days, tropical nights, and dry days well. However, the numbers of hot days and dry days are strongly underestimated and overestimated, respectively, compared to the observations, irrespective of LBCs. The large differences in the simulation skill of RegCM4 for ECEs over South Korea between two simulations can be caused by the differences between two LBCs, ERA and R-2. For the mean climate state, ERA simulates more humidity and warmer temperatures than the R-2, especially in the low-to-mid troposphere, resulting in a warmer and more humid troposphere especially at the central region of the model domain.